2010
DOI: 10.1155/2010/509021
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Expression of TCR Zeta Is Involved in the Abnormal Production of Cytokines by Peripheral T Cells of Patients with Systemic Lupus Erythematosus

Abstract: Accumulating evidence suggests that dysfunction of T cells underlies the pathogenesis of systemic lupus erythematosus (SLE). We revealed that SLE T cells produced an abnormally excessive amount of IFN-γin vitro upon stimulation through TCR, and the expression level of TCR zeta was significantly reduced. The production of IFN-γ by SLE T cells was negatively correlated with the expression level of TCR zeta. This correlation was abolished when the cells were stimulated with TPA and ionomycin, which bypass TCR and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
7
0
1
Order By: Relevance
“…Down-regulation of CD3ζ has also been described in inflammatory or immune mediated diseases including rheumatoid arthritis [48], systemic lupus erythematosus [49] and leprous [50]. Interestingly, in these diseases the down-regulation CD3ζ-chain was associated with reduced IL-2 and IL-2R expression [26], [51], decreased proliferative capacity [52] and high IL-10 secretion [25], [53] on T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Down-regulation of CD3ζ has also been described in inflammatory or immune mediated diseases including rheumatoid arthritis [48], systemic lupus erythematosus [49] and leprous [50]. Interestingly, in these diseases the down-regulation CD3ζ-chain was associated with reduced IL-2 and IL-2R expression [26], [51], decreased proliferative capacity [52] and high IL-10 secretion [25], [53] on T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Whiteside et al reported that TEVs mediate the inhibition of CD3ζ chain expression and drastically reduce its mRNA levels [106]. Decreased expression of the T-cell receptor (TCR) ζ-chain has been reported in several autoimmune, inflammatory and malignant diseases (e.g., lymphoma), and it is commonly associated with suppression of T cell proliferation and altered cytokine production [107,108,109,110]. During cancer progression, T cells are found in close contact with tumor cells and represent an essential component of the TME.…”
Section: Hematological Malignancy-derived Small Evs and Immune Cellsmentioning
confidence: 99%
“…This relationship between CD3ζ levels and cytokine polarization has also been observed in T cells from SLE patients where a negative correlation has been described between CD3ζ levels and IFN-γ production. 23…”
Section: Tcr Signaling In Sle T Cellsmentioning
confidence: 99%